American childhood : a photographic history - Brewster, Todd (Scribner, an imprint of Simon & Schuster, Inc., 2023)
"American childhood is a carefully edited, photographic record of the lives of American children, accompanied by brief, thoughtful essays on aspects of their experiences. There are over 200 pictures of children in this book, ranging over the history of the American nation. Some of the people in these pictures would go on to fame (or infamy). But for the great bulk of them, a photograph is likely the only public trace they have left behind"--